Implementation of Data-Based Pastoral through BIDUK Application to Realize The Living God’s People - Palinoan, Frans Fandy; Tandiangga, Patrio; Arnoltus, Cornelius (Jurnal Ragam Pengabdian, 2024)
The Church is a community of God's people that has a divine and human character because it consists of people who live in a certain time and place. Departing from its human characteristics, the Church Pastoral Pattern is expected to be able to adapt to the situation and real needs of the people. Pastoral actors are expected to be able to work based on data, not assumptions or interpretations without foundation. On the basis of this understanding, the author tries to implement data-based pastoral through the BIDUK application which has begun to be used in the Archdiocese of Makassar, especially in the Renya Rosari Deri Parish. The research method used in this study is a mixed method, in which quantitative data on parishioners recorded in the BIDUK application are collected and processed into a report that describes the real condition of the parishioners, followed by a qualitative theological analysis and reflection on the findings. From the analysis and theological reflection, the author will provide pastoral advice that is expected to provide answers to the needs of the people.